2022
DOI: 10.3389/frma.2022.842670
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Role of Gender in the Relationship Between the Online Payment System and SME Performance: A Case Study Investigating an Emerging Economy—Bangladesh

Abstract: This research examines the moderating role of gender on the adoption of online payment systems (OPS). It also explores the impact of using OPS on the performance of SMEs in an emerging economy, using the Technology Acceptance Model (TAM) and Resource-Based View (RBV). The results indicate that male SME owners (entrepreneurs) are more likely to focus on perceived usefulness, whereas female SME entrepreneurs are more likely to focus on perceived ease of use while adopting OPS, according to data obtained from 302… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Also, uniformity in educational programs or professional training for entrepreneurs may result in a shared level of knowledge and skill in applying AI to business, leading to similar responses. There may be increasing gender parity in entrepreneurship, with women attaining similar levels of empowerment, resource access, and opportunities as their male counterparts, which is reflected in their similar perspectives on AI [15,34,42]. Table 2 presents descriptive statistics and the Mann-Whitney Test results for the AI-enhanced leadership construct.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, uniformity in educational programs or professional training for entrepreneurs may result in a shared level of knowledge and skill in applying AI to business, leading to similar responses. There may be increasing gender parity in entrepreneurship, with women attaining similar levels of empowerment, resource access, and opportunities as their male counterparts, which is reflected in their similar perspectives on AI [15,34,42]. Table 2 presents descriptive statistics and the Mann-Whitney Test results for the AI-enhanced leadership construct.…”
Section: Resultsmentioning
confidence: 99%
“…These innovations can lead to improved work structures and processes, boosting employee health, well-being, and engagement and enhancing overall performance [41]. Also, Nahar [42] found that men and women perceive and use technology differently. For instance, men are often more confident in adopting new technologies and perceive them as more useful than women, who may show hesitancy and lack confidence in using such technologies.…”
Section: Bridging the Gender Divide: Adopting Ai To Reduce Employee W...mentioning
confidence: 99%
“…TAM is amongst the prevalent theories explaining the adoption of new technologies, specifically among micro, small and medium enterprises (MSMEs). To date, prior studies on MSMEs have investigated technology's adoption in various forms, for instance, e-government service [10], [11], mobile banking [12], [13], e-commerce platforms [14], [15], mobile payment [16], [17], enterprise system [18], [19] and social media [20], [21].…”
Section: Introductionmentioning
confidence: 99%